'Can food waste be reduced?' An investigation into food waste management in hospitality industry. (25th September 2020) - Nair, Girish K.; Choudhary, Nidhi; Prasad, Swati
The scope of food wastage is wide. This research paper discusses the aspect of avoidable food wastage in hospitality industries in Qatar. The study seeks to find if the hotels can avoid food wastage through considering their food transportation infrastructure or by considering their food portioning while serving the food to the customers. It even seeks to find if the problem of food wastage in hotels can be trimmed if the consumers change their behaviour in terms of buying, preparing and storing food. Three prominently used concept of food waste management were used in hotel industries have been considered. The research methodology uses interpretivist paradigm using SEM to test the six hypotheses with a sample size of 210 managers chosen from 21 five star hotels. Implications have been drawn to benefit the strategic managers to enhance food waste reduction.